Pengaruh Sistem Informasi Dan Kompetensi Karyawan Terhadap Efektivitas Kerja Karyawan Warehouse - Hendi Sama (Universitas Putera Batam, 2014)
The long term goal of this research is benefiting manufacturing company in Batam regarding effectiveness of employees in doing their job. This research attempts to examine how Information System and Competence of Employees affect Effectiveness of work. This research uses 3 independent variables and 1 dependent variable. The impact of independent variable was analyzed by regression model. Results show that there are significant interrelated dependence relationships among variables.